Parents' future visions for their autistic transition-age youth: Hopes and expectations. (August 2019) - Chen, Jennifer; Cohn, Ellen S; Orsmond, Gael I
Researchers have documented that young adults with autism spectrum disorder have poor outcomes in employment, post-secondary education, social participation, independent living, and community participation. There is a need to further explore contributing factors to such outcomes to better support successful transitions to adulthood. Parents play a critical role in transition planning, and parental expectations appear to impact young adult outcomes for autistic individuals. The aim of this study was to explore how parents express their future visions (i.e. hopes and expectations) for their autistic transition-age youth. Data were collected through focus groups and individual interviews with 18 parents. Parents' hopes and expectations focused on eight primary domains. In addition, parents often qualified or tempered their stated hope with expressions of fears, uncertainty, realistic expectations, and the perceived lack of guidance. We discuss our conceptualization of the relations among these themes and implications for service providers and research.